(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2022)
Cities are literally "taken over" by art. Not only because of the manifestations that can take place in their different theatres, but also by those that invade their streets, parks, squares and corners. We can agree that there is an art designed for the city and another that emerges from them: that emanates substantially. Inverse paths with the same meaning. In the first, there are works that are inscribed by adapting the nature of the artistic language to that of the place. In the second, songs as well as different graffiti that, either writing or illustration, concentrate the pulse of the city. The latest are evidence of this constant desire to express by using the walls as immense canvases to externalise feelings. A timeline that goes from prehistoric times to Mexican muralism up to the present.